(3QSGdI GdGSJjYGH aj GdYed HUOQ GdEhRI hLfGM GdZQGHs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3agPg QSGdI dWjaI eNJUQg SejJgG (B: (3HGdGSJjYGH ddYed HUOQ GdEhRI hLfGM GdZQGH s
(3BNQgG (B:s
(3hCeG EPG WdY Ch ZQH fgGQkG adG aGFOI ajg ZjQ eYQaI GdMce hGddg GYde HGdUhGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B168 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B38 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B135) s
Keywords: (3Gdadcs